Pengaruh Inovasi Kelembagaan Pada Pengembangan Klaster Batik Laweyan Kota Surakarta - Ery Dyah Wulandari (Jurnal Wilayah dan Lingkungan, 2013)
Klaster Batik Laweyan is one of the cluster experienced significant growth as indicated by the existence of institutional innovations in it. This is evident from the condition of the business in the previous Laweyan dim currently being developed due to the formation Forum Pengembangan Kampoeng Batik Laweyan the container in cluster development. This study raises the question "How do innovation institutions affect to the development of Klaster Batik Laweyan?". To answer this research question, the research approach used was qualitative descriptive survey method. This method was chosen because it can explore deeper into the information needed to answer the research objectives. Data was collected through interviews and field observations. The analysis was done by descriptive qualitative analysis method to the analysis stage changes Batik Laweyan Cluster and institutional innovation analysis. The results showed the influence of institutional innovation in the development of Batik Laweyan Cluster. This is indicated by the growing sense of comfort and trust in the new social ties between members of a cluster, among others, the receipt or agreement on common goals Forum Pengembangan Klaster Batik Laweyan (FPKBL) as an order or a new norm in institutional management Batik Laweyan. It was influential in the development of clusters as indicated by the increase in the capacity of members to collaborate, innovate business and increased efforts in Laweyan supporting emerging businesses. As well as the growing cluster networking externally with travel agencies and tourism, academic, private sector, NGOs and the government.